2007
DOI: 10.1001/archneur.64.4.576
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, Caffeine, and Nonsteroidal Anti-inflammatory Drugs in Families With Parkinson Disease

Abstract: To assess associations between Parkinson disease (PD) and putatively protective factors-smoking, caffeine (coffee, tea, and soft drinks), and nonsteroidal antiinflammatory drugs (aspirin, ibuprofen, and naproxen). Design: Family-based case-control study. Setting: Academic medical center clinic. Participants: A total of 356 case subjects and 317 family controls who self-reported environmental exposures. Main Outcome Measures: Associations between PD and environmental measures (history, status, dosage, duration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 16 publications
6
66
1
1
Order By: Relevance
“…As mentioned above, the two largest such studies confirmed the inverse association and also reported a dose-response relationship, indicating that confounding by genetic factors is unlikely [427,435]. Similarly, a case-control study that used siblings as controls reported a significant inverse association between smoking and PD with a dose-response relationship [447], a result that was confirmed in an expanded dataset [448].…”
Section: Suggested Systemic Biases In Studies Of Smoking and Pdmentioning
confidence: 66%
See 1 more Smart Citation
“…As mentioned above, the two largest such studies confirmed the inverse association and also reported a dose-response relationship, indicating that confounding by genetic factors is unlikely [427,435]. Similarly, a case-control study that used siblings as controls reported a significant inverse association between smoking and PD with a dose-response relationship [447], a result that was confirmed in an expanded dataset [448].…”
Section: Suggested Systemic Biases In Studies Of Smoking and Pdmentioning
confidence: 66%
“…Two population-based case-control studies [560,561] and a family-based case-control study [448] found no association between NSAIDs or aspirin and PD. A hospital-based study, in which most controls were spouses or relatives of PD cases, reported lower PD risk associated with use of over the counter NSAIDs (OR 0.81, 95% CI 0.67-0.98 for ever versus never use), with no dose-response relationship [416].…”
Section: Inflammationmentioning
confidence: 98%
“…For missing inputs, Cochrane effectiveness inputs from a wide range of studies world‐wide were used, and represented rigorous and well‐accepted evidence. Some reported but controversial protective effects of smoking, such as those regarding Parkinson disease 63, 64, 65, 66, 67, 68, 69, 70, 71, were not accounted for in this model. Some diseases attributable to smoking 5 were also not included in the model, as the true impact of smoking could not be estimated, and some interventions available only in the United Kingdom but not in Germany were also not considered.…”
Section: Discussionmentioning
confidence: 99%
“…Large scale epidemiological studies have shown that the chronic use of non-steroidal anti-inflammatory drugs (NSAID) such as aspirin or ibuprofen could provide some level of protection against PD (Chen et al, 2005;Chen et al, 2003). Other studies suggest that the role of NSAIDs in decreasing the risk of PD is extremely limited (Hancock et al, 2007;Hernan et al, 2006). A recent meta-analysis of studies published between 1966 and 2008 showed that while NSAIDs as a class do not modify the risk of developing PD, the chronic intake of ibuprofen may have a beneficial effect (Gagne & Power, 2010;Gao et al, 2011;Samii et al, 2009).…”
Section: Immunomodulatory Therapiesmentioning
confidence: 99%